Leveraging Farmer Producer Companies to Transition to Market-Based Production Systems in Jharkhand - Sethy, Paresh; Bihari, Bipin (World Bank, Washington, DC, 2020)
Small and marginal farmers in India struggle for access to good quality inputs in farming of crops (seeds, fertilizers, crop protection) and livestock (stock species, breed, density, feed consumption); credit; market acceptance (such as for a new product); connectivity (for bulk marketing); and storage facilities. Aggregation of farmers into Farmer Producer Companies (FPCs) has shown to overcome many of these problems. JOHAR FPCs are unique compared to existing ones because of their huge membership base (7,000–8,000 per FPC), shareholder composition (only women), and product basket with produce that helps double incomes. This note includes experiences and learnings of the implementation of marketing initiatives for: (i) a new poultry product, and (ii) increasing the marketing of tomato produce through post-harvest management practices and technologies.